Unveiling the causal effects of gut microbiome on trimethylamine N-oxide: evidence from Mendelian randomization - Yu, Yunfeng; Yin, Yuman; Deng, Juan; Yang, Xinyu; Bai, Siyang; Yu, Rong (Frontiers in Microbiology, 2024)
Objective: The relationship between gut microbiome and trimethylamine oxide (TMAO) has not been fully elucidated. We aimed to assess the causal effects of different gut microbes on TMAO using Mendelian randomization (MR). Methods: Gut microbiome and TMAO datasets were acquired from genome-wide association studies and screened for single nucleotide polymorphisms according to the basic assumptions of MR. Inverse variance weighted was used as the main method in MR analysis to assess the causal relationship between the gut microbiome and TMAO. Finally, the MR-Egger intercept, Cochran's Q test, and leave-one-out sensitivity analysis were used to assess the horizontal pleiotropy, heterogeneity, and robustness of the results, respectively. Results: MR analysis revealed that the species Bacteroides finegoldii (odds ratio [OR] 1.064, 95% confidence interval [CI] 1.003 to 1.128, p = 0.039), family Sutterellaceae (OR 1.188, 95% CI 1.003 to 1.407, p = 0.047) and phylum Pseudomonadota (OR 1.205, 95% CI 1.036 to 1.401, p = 0.016), as well as the species Bacteroides uniformis (OR 1.263, 95% CI 1.039 to 1.535, p = 0.019), were positively associated with increased genetic susceptibility to TMAO. In contrast, the species Bacteroides thetaiotaomicron (OR 0.813, 95% CI 0.696 to 0.950, p = 0.009) and Bilophila wadsworthia (OR 0.828, 95% CI 0.690 to 0.995, p = 0.044) were associated with reduced genetic susceptibility to TMAO. Additionally, the MR-Egger intercept indicated no horizontal pleiotropy (p ≥ 0.05), and Cochran's Q test and sensitivity analysis demonstrated that the results were not heterogeneous (p ≥ 0.05) and were robust. Conclusion: Our findings revealed the role of the phylum Pseudomonadota, family Sutterellaceae, species Bacteroides finegoldii, and Bacteroides uniformis in increasing TMAO, as well as the species Bacteroides thetaiotaomicron and Bilophila wadsworthia in decreasing TMAO. This study provides new insights into the relationship between the gut microbiome and TMAO levels.